The United States and Germany in the era of the Cold War, 1945-1990. a handbook - Junker, Detlef; Gassert, Philipp; Mausbach, Wilfried, 1964-; Morris, David B. (David Brian), 1963- (Publications of the German Historical Institute., 2004)
These volumes were originally published in 2004. The close association between the United States and the Federal Republic of Germany was a key element in the international order of the Cold War era. No country had as wide-reaching or as profound an impact on the western portion of divided Germany as the United States. No country better exemplified the East-West conflict in American thinking than Germany. The United States and Germany in the Era of the Cold War examines all facets of German-American relations and interaction in the decades from the defeat of the Third Reich to Germany's reunification in 1990. In addition to its comprehensive treatment of US-West German political, economic, social, and cultural ties, The United States and Germany in the Era of the Cold War provides an overview of the more limited dealings between the US and the communist German Democratic Republic.